Hypothetically virtual approaches to the analysis of the mechanisms of neuropsychic activity - Y. A. Alexandrovsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
The main ideas of the book «the Call and all the rest» [1] and of the separately published «the Unexplored and Unexamined» chapters [2] on non-standard  and not always well grounded approaches to the understanding  of neuro-mental  activity. «Staged» questions are considered and their solution cannot be completed without careful research study. It is proposed to use the following hypothetically formulated postulates:1. Life processes that provide neuropsychic activity cannot be explained only by traditionally understood reflex mechanisms.2. Any living structure  has the  biological ability not  only to  passively absorb  information,  but  also to actively seek it out.3. The conductor  system uses muscle energy in every reflex action. Higher mental activity is formed by other energetic, both exogenous and endogenous flows.4. Conscious (and perhaps not  conscious) life events and behavioral experiences do not  disappear from the functional «memory library».5. Evolutionary unification, despite situational confrontations, is a vital necessity of the interaction process. Its neblinensis parts fall out of the further development cycle. This pattern  determines the general theory of unification and development for biology and sociology.